A monolithic column for adsorbing heavy metals and preparation method thereof
By using a whole column with specific structural compounds and ferrous sulfide, dissociation of complex heavy metals and recycling of heavy metal resources is achieved, and the problems of poor heavy metal removal effect and waste of resources in the prior art are solved.
Patent Information
- Application Number
- CN202411872236.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-04
AI Technical Summary
Existing materials that adsorb heavy metals cannot dissociate complex heavy metals and recover heavy metal resources at the same time, resulting in poor heavy metal removal effect and waste of resources.
Using a monolithic column including a specific structural compound and ferrous sulfide, the complexed heavy metal is dissociated by chelation and replacement reactions and the heavy metal is recovered by elution of the acid solution.
The effective removal of complex heavy metals and the recovery of heavy metal resources are achieved, while improving the adsorption capacity and material regeneration ability.
Smart Images

Figure CN119746826A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wastewater treatment, and in particular to a monolithic column for adsorbing heavy metals and a preparation method thereof. Background Art
[0002] Heavy metals exist in water mainly in the form of ions and complexes. Ionic heavy metals can be effectively removed by adding alkali precipitation. However, in recent years, with the continuous advancement of surface treatment technology, the rapid development of the electroplating industry has led to the discharge of a large amount of wastewater containing heavy metals. Since the composition of electroplating wastewater pollutants is very complex, containing organic complexing agents such as ethylenediaminetetraacetic acid (EDTA), triethanolamine (TEA), tartaric acid and citric acid, heavy metal ions such as copper, nickel, and chromium in the wastewater accept electron pairs from the functional groups in the complexing agent (such as carboxyl, amino, phenolic hydroxyl and thiol, etc.), and strongly bind to the complexing agent, thereby forming a stable complex state. Due to the stable structure of complexed heavy metals, it is difficult to remove complexed heavy metals. At present, the methods for treating complexed heavy metal wastewater include redox method, chemical precipitation method, adsorption separation method and chelation method, but chemical precipitation method, redox method and chelation method need to add reagents to the wastewater, causing secondary pollution of the wastewater, and the removal effect of heavy metals is not ideal.
[0003] Adsorption separation is the most actively studied and applied treatment method for removing toxic pollutants from wastewater. The adsorption separation function of adsorbent materials is to use porous solid compounds to effectively separate and enrich one or several components from a multiphase complex system through physical or chemical methods. The prior art discloses a heavy metal adsorbent and its preparation method and application. The heavy metal adsorbent is prepared by using an inorganic mineral modified by a surfactant as a carrier and loading an organic complexing agent, which can increase the adsorption amount of heavy metals, but it can neither dissociate the complexed heavy metals nor degrade the complexing ligands, resulting in poor effect in reducing the heavy metal content in wastewater. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defect that the adsorption materials for adsorbing heavy metals in the prior art cannot simultaneously achieve the dissociation of complexed heavy metals, resulting in poor heavy metal removal effect, thereby providing an integral column for adsorbing heavy metals and a preparation method thereof.
[0005] Another technical problem solved by the present invention is that the heavy metal adsorption material in the prior art cannot recover the heavy metals after adsorbing the heavy metals in the wastewater, resulting in a waste of resources, thereby providing a monolithic column for adsorbing heavy metals and a preparation method thereof.
[0006] In one aspect, the present invention provides a monolithic column for adsorbing heavy metals, comprising a compound having a structure shown in formula (I) and ferrous sulfide.
[0007]
[0008] Wherein, R1 is selected from C1-C6 alkylene, and the value of n ranges from 10000 to 30000.
[0009] The porosity of the monolithic column is 73-95%.
[0010] In some embodiments, R1 in formula (I) is selected from at least one of methylene and ethylene.
[0011] On the other hand, the present invention also provides a method for preparing a monolithic column for adsorbing heavy metals, comprising the following steps:
[0012] S1, mixing a heavy metal capture agent, a cross-linking agent and a porogen to form a monomer solution, and injecting the monomer solution into a chromatography column, wherein the porogen is water, and the total mass of the heavy metal capture agent and the cross-linking agent is 3%-7% of the monomer solution;
[0013] S2, in the presence of an initiator and a catalyst, at a certain cooling rate, lowering the temperature of the monomer solution to a first temperature and then maintaining it for a first time to form a monolithic column for adsorbing heavy metals, wherein the cooling rate is 0.15°C / min to 0.45°C / min;
[0014] The preparation method of the heavy metal capture agent is as follows: in the presence of an inert gas, at a second temperature, N-hydroxyalkyl acrylamide, carbon disulfide, metal sulfide and ferrous salt are mixed and reacted for a second time to obtain the heavy metal capture agent.
[0015] The heavy metal capture agent comprises a compound having a structure shown in formula (II) and ferrous sulfide.
[0016]
[0017] In some embodiments, the first temperature is -40°C to -15°C, and the first time is 8-18 hours.
[0018] In some of the embodiments, in step S1, the heavy metal capture agent, cross-linking agent and porogen are stirred at a speed of 200-500 rpm for 1-2 hours, and then the heavy metal capture agent, cross-linking agent and porogen are treated under ultrasonic treatment for 10-30 minutes, and the frequency of the ultrasonic treatment is 50-100 kHz.
[0019] In some of the embodiments, the mass ratio of the heavy metal capture agent to the cross-linking agent is (5-8):1.
[0020] In some embodiments, the mass of the initiator is 0.2%-0.5% of the total mass of the heavy metal scavenger and the cross-linking agent.
[0021] In some embodiments, the mass of the catalyst is 0.2%-0.7% of the total mass of the heavy metal capture agent and the cross-linking agent.
[0022] In some embodiments, the cross-linking agent includes at least one of an aldehyde-containing organic substance or an amine-containing organic substance.
[0023] In some embodiments, the initiator comprises a persulfate.
[0024] Preferably, the initiator includes ammonium persulfate, potassium persulfate, and sodium persulfate.
[0025] In some embodiments, the catalyst includes at least one of an organic amine compound and an organic nitrile compound.
[0026] Preferably, the catalyst comprises tetramethylethylenediamine, dimethylpropionitrile, and ethylenediamine.
[0027] In some embodiments, the cross-linking agent includes N,N-methylenebisacrylamide, glutaraldehyde, aminoethylethanolamine, and diethylaminopropylamine.
[0028] In some embodiments, the second temperature is less than or equal to 50° C., preferably 20-45° C., and the second time is 1-3 hours.
[0029] In some embodiments, the molar ratio of N-hydroxyalkyl acrylamide, carbon disulfide and ferrous salt is 1:(2-3):(1-1.8),
[0030] The molar ratio of the sulfide to the ferrous salt is 1:(1-1.3),
[0031] In some of the embodiments, the method for preparing the N-hydroxyalkyl acrylamide solution is to mix an aqueous acrylamide solution, an inhibitor and a hydroxyalkylating agent at a second temperature under alkaline conditions to obtain N-hydroxyalkyl acrylamide.
[0032] In some embodiments, the concentration of the acrylamide aqueous solution is 50-100 g / L.
[0033] In some embodiments, the amount of the polymerization inhibitor added is 100-200 ppm based on the mass of acrylamide.
[0034] In some embodiments, the molar ratio of acrylamide to hydroxyalkyl reagent is 1:(0.8-1.4).
[0035] In some embodiments, the inhibitor includes at least one of N-nitrosodiphenylamine, phenothiazine, hydroquinone, and p-hydroxyanisole.
[0036] Preferably, the polymerization inhibitor includes any two of N-nitrosodiphenylamine, phenothiazine, hydroquinone, and p-hydroxyanisole.
[0037] It should be noted that the inhibitor does not react with the raw materials in the reaction system, and its presence in the reaction system will not affect the formation of the monolithic column for adsorbing heavy metals.
[0038] In some embodiments, the hydroxyalkyl reagent is at least one of formaldehyde or ethylene oxide.
[0039] In some embodiments, the hydroxyalkyl reagent is used in the preparation of N-hydroxyalkyl acrylamide in the form of a solution, wherein the hydroxyalkyl reagent in the aqueous solution is 30-40 wt %.
[0040] In some of the embodiments, the pH value of the reaction solution in the preparation method of N-hydroxyalkyl acrylamide is 9-11.
[0041] In some embodiments, the second temperature is 20-70°C. In order to avoid polycondensation of the hydroxyalkyl reagent, in the embodiments of the present invention, the second temperature is preferably 40-50°C.
[0042] In some of the embodiments, the acrylamide aqueous solution, the polymerization inhibitor and the hydroxyalkyl reagent are mixed under stirring, the stirring rate is 300-500 rpm, and the stirring time is 1-2 hours.
[0043] In some embodiments, the N-hydroxyalkyl acrylamide is at least one of N-hydroxymethyl acrylamide and hydroxyethyl acrylamide.
[0044] In some embodiments, the metal sulfide includes at least one of sodium sulfide and potassium sulfide.
[0045] The technical solution of the present invention has the following advantages:
[0046] 1. The present invention provides a monolithic column for adsorbing heavy metals, wherein the monolithic column comprises a compound having a structure shown in formula (I) and ferrous sulfide,
[0047]
[0048] Wherein, R1 is selected from C1-C6 alkylene, n has a value range of 10000-30000, and the porosity of the monolithic column is 73-95%. The present invention utilizes a polymer having dual active sulfur atoms and acrylamide groups and ferrous sulfide to form a monolithic column for adsorbing heavy metals, the monolithic column has strong chelating performance for complexed heavy metals, and can be connected with heavy metal coordination bonds, while the monolithic column chelates the complexed heavy metals, the ferrous sulfide in the monolithic column competitively replaces the heavy metal ions of the complexed heavy metals, on the one hand, the decomposition of the heavy metals and organic ligands in the complexed heavy metals is achieved, on the other hand, the monolithic column adsorbed with heavy metals is eluted by an acid solution, the resource recovery of heavy metals can be achieved, and the regeneration of the monolithic column is achieved at the same time, and the regenerated monolithic column can continue to adsorb heavy metals. Furthermore, the ferrous sulfide in the monolithic column for heavy metal adsorption provided by the present invention captures dissolved oxygen in water to generate hydroxyl radicals with strong oxidizing effect in situ, which can degrade organic ligands, avoid the existence of organic ligands and the subsequent inflow of heavy metals to continuously generate complex heavy metals, and achieve sustainable reduction of the content of complex heavy metals. At the same time, the monolithic column for heavy metal adsorption provided by the present invention has a porosity of 73-95%, uniform distribution and good connectivity. The monolithic column can withstand high back pressure, has low flow resistance and large adsorption capacity, and can improve the adsorption rate of heavy metals and will not cause an increase in total organic carbon content.
[0049] Therefore, the monolithic column for adsorbing heavy metals provided by the present invention can not only realize the chelation of complexed heavy metals, but also realize the separation of organic ligands and heavy metals in complexed heavy metals and the degradation of organic ligands, and can also recover heavy metals.
[0050] 2. The present invention provides a method for preparing a monolithic column for adsorbing heavy metals, comprising the following steps: S1, mixing a heavy metal scavenger, a cross-linking agent and a porogen to form a monomer solution, and injecting the monomer solution into a chromatography column, wherein the porogen is water, and the total mass of the heavy metal scavenger and the cross-linking agent is 3%-7% of the monomer solution; S2, in the presence of an initiator and a catalyst, at a certain cooling rate, reducing the temperature of the monomer solution to a first temperature and then maintaining it for a first time to form a monolithic column for adsorbing heavy metals, wherein the cooling rate is 0.15°C / min to 0.45°C / min; wherein the method for preparing the heavy metal scavenger is that, in the presence of an inert gas, at a second temperature, N-hydroxyalkyl acrylamide, carbon disulfide, metal sulfide and ferrous salt are mixed, and reacted for a second time to obtain the heavy metal scavenger. The present invention first forms a heavy metal capture agent through N-hydroxyalkyl acrylamide, carbon disulfide, sulfide and ferrous salt. The formed heavy metal capture agent has a compound of formula (II) and ferrous sulfide. The compound with the structure shown in formula (II) is used as a monomer material. The pore-forming agent undergoes a crystal phase change during the slow cooling process to form pores on the monomer. At the same time, under the action of an initiator and a catalyst, the monomer slowly polymerizes at low temperature to generate a linear polymer. Since a cross-linking agent is added to the reaction system, the cross-linking agent is attacked by carbon cations, so cross-linking is formed between single chains, and a three-dimensional spatial network structure is finally formed. At the same time, the formed polymer and the ferrous sulfide in the heavy metal capture agent form a monolithic column for adsorbing heavy metals. In the present invention, the compound with the structure shown in formula (II) is used as a monomer, and the monomer solution undergoes a crystal phase change reaction and a polymerization reaction at the same time to obtain a monolithic column with a pore structure, which increases the active sites of the adsorption function and improves the adsorption capacity of the complexed heavy metal. The monolithic column for adsorbing heavy metals prepared by the present invention is not only elastic in water, but also has suitable mechanical strength.
[0051] 3. The preparation method of the monolithic column for heavy metal adsorption provided by the present invention, the mass ratio of the heavy metal scavenger to the cross-linking agent is (5-8): 1; the total mass of the heavy metal scavenger and the cross-linking agent in step S1 is 3-7% of the monomer solution. If the concentration of the heavy metal scavenger is too high, the density of the prepared material is large and the pores are small, which is not conducive to the adsorption of heavy metals. If the concentration of the heavy metal scavenger is too low, the skeleton of the monolithic column for heavy metal adsorption is thin and the mechanical strength is poor. During use, the structural instability causes the filler in the monolithic column to break. The present invention can keep the pores of the monolithic column for heavy metal adsorption large by controlling the raw material concentration of the heavy metal scavenger, and the skeleton of the monolithic column for heavy metal adsorption is stable, and the heavy metal adsorption effect is good. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0053] Figure 1 This is the infrared spectrum of the compound having the structure shown in formula (III) in the heavy metal scavenger of Preparation Example 1 of the present invention;
[0054] Figure 2 This is the infrared spectrum of the compound having the structure shown in formula (V) in the monolithic column for adsorbing heavy metals in Example 1 of the present invention. DETAILED DESCRIPTION
[0055] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0056] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0057] Preparation Example 1
[0058] This preparation example provides a preparation method of a heavy metal scavenger, and the specific steps and parameters are as follows:
[0059] (1) 7 g of acrylamide was weighed into a reactor, and 100 mL of deionized water was added. The stirring speed was controlled at 400 rpm. 100 ppm of N-nitrosodiphenylamine (compared to the mass of acrylamide), 50 ppm of phenothiazine (compared to the mass of acrylamide), and 10 mL of a formaldehyde solution with a formaldehyde concentration of 30 wt % were added in sequence. The reaction pH was adjusted to 10 with 10 wt % of sodium hydroxide. The temperature of the entire reaction system was controlled at 50° C. and the reaction was carried out for 1.5 h to prepare N-hydroxymethyl acrylamide.
[0060] (2) The reactor of step (1) was sealed, and nitrogen was continuously introduced into the reactor for protection. 15 mL of carbon disulfide was added dropwise into the reactor at a flow rate of 200 μL / min using a microinjector, and 55 mL of a 50 wt% aqueous solution of ferrous sulfate heptahydrate and 12 mL of a 50% sodium sulfide were added dropwise into the reactor at a flow rate of 800 μL / min. The reaction temperature was controlled within 50° C. After the addition, the reaction was continued to stir for 2 h to obtain a light green liquid, which was a heavy metal scavenger.
[0061] The heavy metal scavenger prepared in this preparation example includes a compound represented by formula (III) and ferrous sulfide.
[0062]
[0063] The compound represented by formula (III) in the heavy metal scavenger prepared in this preparation example was subjected to infrared measurement, and the infrared spectrum of the measurement is shown in FIG. Figure 1 , among which, 1900-1650cm -1 Characteristic peaks appear in the range of -C=O-; 1690-1500cm -1 Characteristic peaks appear in the range of -C=C-; 1100-1000cm -1 Characteristic peaks appear in the range of 700-600cm -1 A characteristic peak appears within the range, indicating the presence of -CS- on the surface.
[0064] Preparation Example 2
[0065] This preparation example provides a preparation method of a heavy metal scavenger, and the specific steps and parameters are as follows:
[0066] (1) 7 g of acrylamide was weighed into a reactor, and 100 mL of deionized water was added. The stirring speed was controlled at 400 rpm. 100 ppm of N-nitrosodiphenylamine (compared to the mass of acrylamide), 50 ppm of phenothiazine (compared to the mass of acrylamide), and 10 mL of a formaldehyde solution with a formaldehyde concentration of 30 wt % were added in sequence. The reaction pH was adjusted to 10 with 10 wt % of sodium hydroxide. The temperature of the entire reaction system was controlled at 50° C. and the reaction was carried out for 1.5 h to prepare N-hydroxymethyl acrylamide.
[0067] (2) The reactor of step (1) was sealed, and nitrogen was continuously introduced into the reactor for protection. 12.5 mL of carbon disulfide was added dropwise into the reactor at a flow rate of 200 μL / min using a microinjector, and 66 mL of a 50 wt% aqueous solution of ferrous sulfate heptahydrate and 20 mL of a 50% sodium sulfide were added dropwise into the reactor at a flow rate of 800 μL / min. The reaction temperature was controlled within 50° C. After the addition, the reaction was continued to stir for 2 h to obtain a light green liquid, which was a heavy metal scavenger.
[0068] Preparation Example 3
[0069] This preparation example provides a preparation method of a heavy metal scavenger, and the specific steps and parameters are as follows:
[0070] (1) 7 g of acrylamide was weighed into a reactor, and 100 mL of deionized water was added. The stirring speed was controlled at 400 rpm. 100 ppm of N-nitrosodiphenylamine (compared to the mass of acrylamide), 50 ppm of phenothiazine (compared to the mass of acrylamide), and 10 mL of a formaldehyde solution with a formaldehyde concentration of 30 wt % were added in sequence. The reaction pH was adjusted to 10 with 10 wt % of sodium hydroxide. The temperature of the entire reaction system was controlled at 50° C. and the reaction was carried out for 1.5 h to prepare N-hydroxymethyl acrylamide.
[0071] (2) The reactor of step (1) was sealed, and nitrogen was continuously introduced into the reactor for protection. 18 mL of carbon disulfide was added dropwise into the reactor at a flow rate of 200 μL / min using a microinjector, and 37 mL of a 50 wt% aqueous solution of ferrous sulfate heptahydrate and 8.5 mL of a 50% sodium sulfide were added dropwise into the reactor at a flow rate of 800 μL / min. The reaction temperature was controlled within 50° C. After the addition, the reaction was continued to stir for 2 h to obtain a light green liquid, which was a heavy metal scavenger.
[0072] Preparation Example 4
[0073] This preparation example provides a preparation method for a heavy metal scavenger. The specific steps and parameters are the same as those in Preparation Example 1, except that 10 mL of 30 wt % ethylene oxide solution is used instead of the formaldehyde solution in step (1).
[0074] The heavy metal scavenger prepared in this preparation example includes a compound represented by formula (IV) and ferrous sulfide.
[0075]
[0076] Example 1
[0077] This embodiment provides a method for preparing a monolithic column for adsorbing heavy metals. The specific steps and methods are as follows:
[0078] (1) The cross-linking agent N,N-methylenebisacrylamide, the heavy metal scavenger prepared in Preparation Example 1 and deionized water were stirred at 300 rpm for 1.5 h, and then the mixture was ultrasonically treated at 50 kHz for 10 min to form a monomer solution, wherein the compound represented by formula (III) in the heavy metal scavenger was used as the monomer, wherein the mass ratio of the monomer to N,N-methylenebisacrylamide was 7:1, and the total mass of the monomer and the cross-linking agent was 5wt% of the monomer solution. The formed monomer solution was pre-cooled at 4°C for later use.
[0079] (2) The initiator and the catalyst were dissolved in deionized water respectively, and pre-cooled at 4° C. for later use, wherein the initiator was sodium persulfate, and the mass of the initiator was 0.3% of the total mass of the monomer and the cross-linking agent; the catalyst was tetramethylethylenediamine, and the amount of the catalyst added was 0.5% of the total mass of the monomer and the cross-linking agent.
[0080] (3) The initiator and the catalyst were sequentially added to the monomer solution using a vortex mixer and shaken for 5 seconds. The mixture was poured into a chromatography column (diameter of the chromatography column was 5 cm and height was 30 cm), and the temperature was reduced at a rate of 0.30°C / min to -18°C. The reaction was maintained for 12 hours, thawed at room temperature, and rinsed with deionized water to obtain a monolithic column for adsorbing heavy metals.
[0081] The monolithic column for adsorbing heavy metals prepared in this embodiment includes a compound represented by formula (V) and ferrous sulfide.
[0082]
[0083] The molecular weight of the compound represented by formula (V) in the monolithic column for adsorbing heavy metals prepared in this embodiment was determined by gel permeation chromatography (GPC) to be 7 million, and the degree of polymerization n was 2×10 4 .
[0084] The compound represented by formula (V) in the monolithic column for adsorbing heavy metals prepared in this example was subjected to infrared measurement, and the infrared spectrum of the measurement is shown in FIG. Figure 2 , and Figure 1 In comparison, it can be seen that Figure 2 Missing 1545.51cm -1 The characteristic peak of the wave number proves that the polymer of this example is a product obtained by the breaking addition polymerization of the carbon-carbon double bonds of the monomers.
[0085] Example 2
[0086] This embodiment provides a method for preparing a monolithic column for adsorbing heavy metals. The specific steps and methods are the same as those in Example 1, except that in step (1), the total mass of the monomer and the cross-linking agent is 3 wt % of the monomer solution.
[0087] The molecular weight of the compound represented by formula (V) in the monolithic column for adsorbing heavy metals prepared in this embodiment was determined by gel permeation chromatography (GPC) to be 6.5 million, and the degree of polymerization n was 1×10 4 .
[0088] Example 3
[0089] This embodiment provides a method for preparing a monolithic column for adsorbing heavy metals. The specific steps and methods are the same as those in Example 1, except that in step (1), the total mass of the monomer and the cross-linking agent is 7 wt % of the monomer solution.
[0090] The molecular weight of the compound represented by formula (V) in the monolithic column for adsorbing heavy metals prepared in this embodiment was determined by gel permeation chromatography (GPC) to be 7.8 million, and the degree of polymerization n was 3×10 4 .
[0091] Example 4
[0092] This embodiment provides a method for preparing a monolithic column for adsorbing heavy metals. The specific steps and methods are the same as those in Example 1, except that the mass of the initiator in step (2) is 0.2% of the total mass of the monomer and the cross-linking agent.
[0093] Example 5
[0094] This embodiment provides a method for preparing a monolithic column for adsorbing heavy metals. The specific steps and methods are the same as those in Example 1, except that the mass of the initiator in step (2) is 0.5% of the total mass of the monomer and the cross-linking agent.
[0095] Example 6
[0096] This embodiment provides a method for preparing a monolithic column for adsorbing heavy metals. The specific steps and methods are the same as those in Example 1, except that the amount of catalyst added in step (2) is 0.2% of the total mass of the monomer and the cross-linking agent.
[0097] Example 7
[0098] This embodiment provides a method for preparing a monolithic column for adsorbing heavy metals. The specific steps and methods are the same as those in Example 1, except that the amount of catalyst added in step (2) is 0.7% of the total mass of the monomer and the cross-linking agent.
[0099] Example 8
[0100] This embodiment provides a method for preparing a monolithic column for adsorbing heavy metals. The specific steps and methods are the same as those in Example 1, except that the cooling rate in step (3) is 0.15° C. / min.
[0101] Example 9
[0102] This embodiment provides a method for preparing a monolithic column for adsorbing heavy metals. The specific steps and methods are the same as those in Example 1, except that the cooling rate in step (3) is 0.45°C / min.
[0103] Example 10
[0104] This embodiment provides a method for preparing a monolithic column for adsorbing heavy metals. The specific steps and methods are the same as those in Example 1, except that the heavy metal scavenger prepared in Preparation Example 4 is used to replace the heavy metal scavenger in step (1) as a monomer.
[0105] The monolithic column for adsorbing heavy metals prepared in this embodiment includes a compound represented by formula (VI) and ferrous sulfide.
[0106]
[0107] The molecular weight of the compound represented by formula (VI) in the monolithic column for adsorbing heavy metals prepared in this embodiment was determined by gel permeation chromatography (GPC) to be 7 million, and the degree of polymerization n was 1.5×10 4 .
[0108] Embodiment 11
[0109] This embodiment provides a method for preparing a monolithic column for adsorbing heavy metals. The specific steps and methods are as follows:
[0110] (1) The cross-linking agent glutaraldehyde, the heavy metal scavenger prepared in Preparation Example 1 and deionized water were stirred at 500 rpm for 1 hour, and then the mixture was ultrasonically treated at 100 kHz for 10 minutes to form a monomer solution, wherein the compound represented by formula (III) in the heavy metal scavenger prepared in Preparation Example 1 was used as a monomer, wherein the mass ratio of the monomer to glutaraldehyde was 5:1, and the total mass of the monomer and the cross-linking agent was 5wt% of the monomer solution, and the formed monomer solution was pre-cooled at 4°C for use.
[0111] (2) The initiator and the catalyst were dissolved in deionized water respectively, and precooled at 4° C. for later use, wherein the initiator was ammonium persulfate, and the mass of the initiator was 0.3% of the total mass of the monomer and the cross-linking agent; the catalyst was dimethylpropionitrile, and the amount of the catalyst added was 0.5% of the total mass of the monomer and the cross-linking agent.
[0112] (3) The initiator and the catalyst were sequentially added to the monomer solution using a vortex mixer and shaken for 5 seconds. The mixed solution was poured into a chromatography column (diameter of the chromatography column was 5 cm and height was 30 cm). The temperature was lowered at a rate of 0.30°C / min until the temperature dropped to -15°C. The reaction was maintained for 18 hours. The mixture was thawed at room temperature and rinsed with deionized water to obtain a monolithic column for adsorbing heavy metals.
[0113] Example 12
[0114] This embodiment provides a method for preparing a monolithic column for adsorbing heavy metals. The specific steps and methods are as follows:
[0115] (1) The cross-linking agent aminoethylethanolamine, the heavy metal scavenger prepared in Preparation Example 1 and deionized water were stirred at 200 rpm for 2 h, and then the mixture was ultrasonically treated at 80 kHz for 30 min to form a monomer solution, wherein the compound represented by formula (III) in the heavy metal scavenger is a monomer, wherein the mass ratio of the monomer to the cross-linking agent is 8:1, and the total mass of the monomer and the cross-linking agent is 5 wt % of the monomer solution, and the formed monomer solution is pre-cooled at 4° C. for use.
[0116] (2) The initiator and the catalyst were dissolved in deionized water respectively, and pre-cooled at 4° C. for later use, wherein the initiator was potassium persulfate, and the mass of the initiator was 0.3% of the total mass of the monomer and the cross-linking agent; the catalyst was ethylenediamine, and the amount of the catalyst added was 0.5% of the total mass of the monomer and the cross-linking agent.
[0117] (3) The initiator and the catalyst were sequentially added to the monomer solution using a vortex mixer and shaken for 5 seconds. The mixed solution was poured into a chromatography column (diameter of the chromatography column was 5 cm and height was 30 cm). The temperature was lowered at a rate of 0.30°C / min until the temperature dropped to -40°C. The reaction was maintained for 8 hours. The mixture was thawed at room temperature and rinsed with deionized water to obtain a monolithic column for adsorbing heavy metals.
[0118] Embodiment 13
[0119] This embodiment provides a method for preparing a monolithic column for adsorbing heavy metals. The specific steps and methods are as follows:
[0120] (1) The cross-linking agent diethylaminopropylamine, the heavy metal scavenger prepared in Preparation Example 1 and deionized water were stirred at 300 rpm for 1.5 h, and then the mixture was ultrasonically treated at 50 kHz for 10 min to form a monomer solution, wherein the compound represented by formula (III) in the heavy metal scavenger was used as the monomer, wherein the mass ratio of the monomer to the cross-linking agent was 7:1, and the total mass of the monomer and the cross-linking agent was 5wt% of the monomer solution, and the formed monomer solution was pre-cooled at 4°C for use.
[0121] (2) The initiator and the catalyst were dissolved in deionized water respectively, and pre-cooled at 4° C. for later use, wherein the initiator was sodium persulfate, and the mass of the initiator was 0.3% of the total mass of the monomer and the cross-linking agent; the catalyst was tetramethylethylenediamine, and the amount of the catalyst added was 0.5% of the total mass of the monomer and the cross-linking agent.
[0122] (3) The initiator and the catalyst were sequentially added to the monomer solution using a vortex mixer and shaken for 5 seconds. The mixture was poured into a chromatography column (diameter of the chromatography column was 5 cm and height was 30 cm), and the temperature was reduced at a rate of 0.30°C / min to -18°C. The reaction was maintained for 12 hours, thawed at room temperature, and rinsed with deionized water to obtain a monolithic column for adsorbing heavy metals.
[0123] Comparative Example 1
[0124] This comparative example provides a method for preparing a monolithic column for adsorbing heavy metals, and the specific steps and methods are as follows:
[0125] (1) The cross-linking agent N,N-methylenebisacrylamide, the heavy metal scavenger prepared in Preparation Example 1 and deionized water were stirred at 300 rpm for 1.5 h, and then the mixture was ultrasonically treated at 50 kHz for 10 min to form a monomer solution, wherein the compound represented by formula (III) in the heavy metal scavenger was used as the monomer, wherein the mass ratio of the monomer to N,N-methylenebisacrylamide was 7:1, and the total mass of the monomer and the cross-linking agent was 5wt% of the monomer solution. The formed monomer solution was pre-cooled at 4°C for later use.
[0126] (2) The initiator and the catalyst were dissolved in deionized water respectively, and pre-cooled at 4° C. for later use, wherein the initiator was sodium persulfate, and the mass of the initiator was 0.3% of the total mass of the monomer and the cross-linking agent; the catalyst was tetramethylethylenediamine, and the amount of the catalyst added was 0.5% of the total mass of the monomer and the cross-linking agent.
[0127] (3) The initiator and the catalyst are sequentially added to the monomer solution using a vortex mixer, and the mixture is shaken for 5 seconds. The mixture is poured into a chromatography column (diameter of the chromatography column is 5 cm, height is 30 cm), and the reaction is maintained at 25° C. for 12 hours. The column is then rinsed with deionized water to obtain a monolithic column for adsorbing heavy metals.
[0128] Comparative Example 2
[0129] This embodiment provides a method for preparing a monolithic column for adsorbing heavy metals. The specific steps and methods are the same as those in Example 1, except that in step (1), the total mass of the monomer and the cross-linking agent is 2 wt % of the monomer solution.
[0130] The pore size of the obtained monolithic column for adsorbing heavy metals is 80-300 μm, the porosity is 98%, and the expansion degree is 14.5 / °C. The test method is shown in Experimental Example 1.
[0131] Comparative Example 3
[0132] This embodiment provides a method for preparing a monolithic column for adsorbing heavy metals. The specific steps and methods are the same as those in Example 1, except that in step (1), the total mass of the monomer and the cross-linking agent is 8 wt % of the monomer solution.
[0133] The pore size of the obtained monolithic column for adsorbing heavy metals is 10-80 μm, the porosity is 53%, and the expansion degree is 5.7 / °C. The test method is shown in Experimental Example 1.
[0134] Comparative Example 4
[0135] This embodiment provides a method for preparing a monolithic column for adsorbing heavy metals. The specific steps and methods are the same as those in Example 1, except that the cooling rate in step (3) is 0.1°C / min.
[0136] The pore size of the obtained monolithic column for adsorbing heavy metals is 20-80 μm, the porosity is 97%, and the expansion degree is 9.45 / °C. The test method is shown in Experimental Example 1.
[0137] Comparative Example 5
[0138] This embodiment provides a method for preparing a monolithic column for adsorbing heavy metals. The specific steps and methods are the same as those in Example 1, except that the cooling rate in step (3) is 0.5°C / min.
[0139] The pore size of the obtained monolithic column for adsorbing heavy metals is 20-80 μm, the porosity is 60%, and the expansion degree is 11.2 / °C. The test method is shown in Experimental Example 1.
[0140] Comparative Example 6
[0141] This comparative example provides a method for preparing a monolithic column for adsorbing heavy metals. The specific steps and parameters are the same as those in Example 1, except that the preparation method of the heavy metal capture agent in step (1) is as follows:
[0142] Take 0.1 mol of acrylamide and put it into a closed reactor, continuously introduce nitrogen protection into it, use a microinjector to drop 15 mL of carbon disulfide at a flow rate of 200 μL / min, add 55 mL of a 50 wt% aqueous solution of ferrous sulfate heptahydrate and 12 mL of a 50% sodium sulfide at a flow rate of 800 μL / min, control the reaction temperature within 50°C, continue to stir the reaction for 2 hours after the addition, and obtain a light green liquid, which is a heavy metal scavenger.
[0143] Comparative Example 7
[0144] This comparative example provides a method for preparing a monolithic column for adsorbing heavy metals. The specific steps and parameters are the same as those in Example 1, except that the preparation method of the heavy metal capture agent in step (1) is as follows:
[0145] 1. Weigh 7 g of acrylamide into a reactor, add 100 mL of deionized water, control the stirring speed to 400 rpm, add 100 ppm of N-nitrosodiphenylamine (compared to the mass of acrylamide), 50 ppm of phenothiazine (compared to the mass of acrylamide), and 10 mL of formaldehyde solution with a formaldehyde concentration of 30 wt %, adjust the reaction pH to 10 with 10 wt % sodium hydroxide, control the temperature of the entire reaction system at 50 ° C, react for 1.5 h, and prepare N-hydroxymethyl acrylamide.
[0146] 2. Seal the reactor of step (1), continuously introduce nitrogen protection into it, use a microinjector to drop 15 mL of carbon disulfide into the reactor at a flow rate of 200 μL / min, and drop 12 mL of 50% sodium sulfide into the reactor at a flow rate of 800 μL / min, control the reaction temperature within 50°C, continue to stir the reaction for 2 hours after the addition, and obtain a light green liquid, which is the heavy metal scavenger.
[0147] Comparative Example 8
[0148] This comparative example provides a method for preparing a monolithic column for adsorbing heavy metals. The specific steps and parameters are the same as those in Example 1, except that the preparation method of the heavy metal capture agent in step (1) is as follows:
[0149] 1. Weigh 7 g of acrylamide into a reactor, add 100 mL of deionized water, control the stirring speed to 400 rpm, add 100 ppm of N-nitrosodiphenylamine (compared to the mass of acrylamide), 50 ppm of phenothiazine (compared to the mass of acrylamide), and 10 mL of formaldehyde solution with a formaldehyde concentration of 30 wt %, adjust the reaction pH to 10 with 10 wt % sodium hydroxide, control the temperature of the entire reaction system at 50 ° C, react for 1.5 h, and prepare N-hydroxymethyl acrylamide.
[0150] 2. The reactor of step (1) was sealed, and nitrogen was continuously introduced therein for protection. 55 mL of 50 wt% aqueous ferrous sulfate heptahydrate solution and 12 mL of 50% sodium sulfide were dripped into the reactor using a microinjector at a flow rate of 800 μL / min. The reaction temperature was controlled within 50° C. After the dripping, the reaction was continued to stir for 2 h to obtain a light green liquid, which was a heavy metal scavenger.
[0151] Experimental Example 1
[0152] The pore size, porosity and expansion degree of the monolithic columns for adsorbing heavy metals prepared in Examples 1-13 and Comparative Examples 1-5 were tested. The results are shown in Table 1.
[0153] Among them, the method for detecting the pore size is as follows: the pore structure size is characterized by a scanning electron microscope (SEM) photograph to obtain an image of the pore structure and size of the crystal gel.
[0154] Porosity detection method: Porosity The volume of the whole column after water absorption and the weight of free water in the pores of the whole column are measured. The specific steps are to first saturate the whole column with water, measure its volume (V0) and wet weight (m w Then squeeze out the free water in the pores and weigh it (m s ), and then calculate as follows:
[0155]
[0156] In the formula, ρ w is the density of deionized water, kg / m 3 .
[0157] Expansion degree detection method: The expansion degree of the whole column (S w / w The specific steps are as follows: first, wash the monolithic column with a large amount of deionized water and then transfer it into a pre-weighed container to measure its wet weight (m w ), and then dry the sample at 60℃ until constant weight is measured (m d ), then the expansion degree of the whole column S w / w It can be calculated by the following formula:
[0158]
[0159] Table 1 Determination of monolithic column performance for heavy metal adsorption
[0160]
[0161]
[0162] According to Table 1, compared with the comparative example, the material prepared by polymerization without low-temperature pore making is in gel column shape and does not have a pore structure, and cannot be used as a filler in the chromatography column. The porosity of the overall column prepared in Comparative Example 2 is 98%, and the porosity of the overall column prepared in Comparative Example 4 is 97%. The overall columns of Comparative Examples 2 and 4 have low mechanical strength. When applied to the overall column, the overall column is soft. When the wastewater is treated, it has been washed and the material is broken. The porosity of the overall column prepared in Comparative Example 3 is 53%, and the porosity of the overall column prepared in Comparative Example 5 is 60%. The overall columns of Comparative Examples 3 and 5 have a large density and dense pores, resulting in a large mass transfer resistance and a long loading time, and the removal of heavy metals in wastewater cannot be achieved.
[0163] Experimental Example 2
[0164] The zinc-nickel alloy wastewater from a certain electroplating park in Ningbo was treated as the target. 2+ 、Ni 2+ The concentrations were 453 mg / L and 63.21 mg / L respectively, the total nitrogen concentration was 1392 mg / L, and the total organic carbon (TOC) concentration was 3240 mg / L.
[0165] The wastewater is passed through the monolithic column for adsorbing heavy metals formed in Examples 1-13 and Comparative Examples 6-8 at a flow rate of 2 ml / min. The zinc ions and nickel ions in the sample solution to be tested are selectively adsorbed on the monolithic column. After the loading is completed, the monolithic column is rinsed with pure water to obtain the first eluent.
[0166] A 2M hydrochloric acid solution is passed through the monolithic column after adsorbing heavy metal ions at a flow rate of 1.5 ml / min to elute the heavy metal ions, and the second eluate is collected to achieve recovery of the heavy metals.
[0167] Detection of Zn in the first eluate by ICP-OES 2+ 、Ni 2+ The concentration of total nitrogen (TN) in water samples was determined by alkaline potassium persulfate ultraviolet spectrophotometry (HJ 636-2012), and the total organic carbon content (TOC) was detected using a total organic carbon analyzer. The results are shown in Table 2.
[0168] Table 2 Performance test results of monolithic columns for adsorbing heavy metals
[0169]
[0170]
[0171] According to the data in Table 2, the monolithic column with a certain pore structure and expansion degree provided by the present invention can be used to remove heavy metals in wastewater, reducing the zinc ion content from 453 mg / L to below 0.19 mg / L, and reducing the nickel ion content from 63.21 mg / L to below 0.15 mg / L. It will not only not cause an increase in the concentration of total nitrogen and total organic carbon, but can reduce the total nitrogen and total organic carbon contents.
[0172] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A monolithic column for adsorbing heavy metals, characterized in that: The monolithic column comprises a compound having a structure shown in formula (I) and ferrous sulfide, Wherein, R1 is selected from C1-C6 alkylene, and the value of n ranges from 10000 to 30000. The porosity of the monolithic column is 73-95%.
2. The monolithic column for adsorbing heavy metals according to claim 1, characterized in that: In formula (I), R1 is at least one selected from methylene and ethylene.
3. A method for preparing a monolithic column for adsorbing heavy metals according to any one of claims 1 to 2, characterized in that: The following steps are included: S1, mixing a heavy metal capture agent, a cross-linking agent and a porogen to form a monomer solution, and injecting the monomer solution into a chromatography column, wherein the porogen is water, and the total mass of the heavy metal capture agent and the cross-linking agent is 3%-7% of the monomer solution; S2, in the presence of an initiator and a catalyst, at a certain cooling rate, lowering the temperature of the monomer solution to a first temperature and then maintaining it for a first time to form a monolithic column for adsorbing heavy metals, wherein the cooling rate is 0.15°C / min to 0.45°C / min; The preparation method of the heavy metal capture agent is as follows: in the presence of an inert gas, at a second temperature, N-hydroxyalkyl acrylamide solution, carbon disulfide, metal sulfide and ferrous salt are mixed and reacted for a second time to obtain the heavy metal capture agent.
4. The method for preparing a monolithic column for adsorbing heavy metals according to claim 3, characterized in that: The first temperature is -40°C to -15°C, and the first time is 8-18 hours; and / or, In step S1, the heavy metal scavenger, cross-linking agent and porogen are stirred at 200-500 rpm for 1 h-2 h, and then treated with ultrasound for 10-30 min, with a frequency of 50 kHz-100 kHz.
5. The method for preparing a monolithic column for adsorbing heavy metals according to claim 4, characterized in that: The mass ratio of the heavy metal capture agent to the cross-linking agent is 5-8:
1.
6. The method for preparing a monolithic column for adsorbing heavy metals according to claim 5, characterized in that: The mass of the initiator is 0.2%-0.5% of the total mass of the heavy metal scavenger and the cross-linking agent; and / or, The mass of the catalyst is 0.2%-0.7% of the total mass of the heavy metal capture agent and the cross-linking agent.
7. The method for preparing a monolithic column for adsorbing heavy metals according to claim 6, characterized in that: The cross-linking agent comprises at least one of an organic substance containing an aldehyde group or an organic substance containing an amine group; and / or, The initiator comprises a persulfate; and / or, The catalyst includes at least one of an organic amine compound and an organic nitrile compound.
8. The method for preparing a monolithic column for adsorbing heavy metals according to claim 7, characterized in that: The cross-linking agent includes N,N-methylenebisacrylamide, glutaraldehyde, aminoethylethanolamine, diethylaminopropylamine; and / or, The initiator comprises at least one of ammonium persulfate, potassium persulfate and sodium persulfate; and / or, The catalyst includes at least one of tetramethylethylenediamine, dimethylpropionitrile and ethylenediamine.
9. The method for preparing a monolithic column for adsorbing heavy metals according to claim 8, characterized in that: The second temperature is less than or equal to 50° C., preferably 20° C.-45° C., and the second time is 1-3 hours; and / or, The molar ratio of the N-hydroxyalkyl acrylamide, carbon disulfide and ferrous salt is 1:2-3:1-1.8, The molar ratio of the metal sulfide to the ferrous salt is 1:1-1.
3.
10. The method for preparing a monolithic column for adsorbing heavy metals according to claim 9, characterized in that: N-hydroxyalkyl acrylamide is at least one of N-hydroxymethyl acrylamide and hydroxyethyl acrylamide, The metal sulfide includes at least one of sodium sulfide and potassium sulfide.